2008
DOI: 10.1158/1078-0432.ccr-08-0611
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Intratumoral Convection: Pressure-Dependent Enhancement in Chemotherapeutic Delivery to Solid Tumors

Abstract: Purpose Low molecular weight (LMW) chemotherapeutics are believed to reach tumors through diffusion across capillary beds as well as membrane transporters. Unexpectedly, the delivery of these agents appears to be augmented by reductions in tumor interstitial fluid pressure (TIFP), an effect typically associated with high molecular weight molecules which reach tumors principally through convection. We investigated the hypothesis that improved intratumoral convection can alter tumor metabolism and enhance the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…The observed elevated Pi concentration in TME of breast tumors vs. normal mammary glands, and in highly metastatic tumor xenografts compared to non-metastatic tumors raises questions about the role of interstitial inorganic phosphate in tumor progression and metastasis. Among the other factors, alterations in interstitial fluid pressure and/or tumor blood flow could influence the amount of inorganic phosphate observed in the extracellular compartment20. We did not observe a difference in the degree of vascularization of the non-metastatic PC14 and metastatic PC14HM tumor xenografts which suggests that this factor may not contribute to the difference in [Pi] between two types of xenograft tumors (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The observed elevated Pi concentration in TME of breast tumors vs. normal mammary glands, and in highly metastatic tumor xenografts compared to non-metastatic tumors raises questions about the role of interstitial inorganic phosphate in tumor progression and metastasis. Among the other factors, alterations in interstitial fluid pressure and/or tumor blood flow could influence the amount of inorganic phosphate observed in the extracellular compartment20. We did not observe a difference in the degree of vascularization of the non-metastatic PC14 and metastatic PC14HM tumor xenografts which suggests that this factor may not contribute to the difference in [Pi] between two types of xenograft tumors (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Survival, in fact, is no more than marginally extended if this combination is administered when they are nearly palpable in the mammary pad (20th wk of age), because it does no more than slow down the progress of a few lesions and reduce the number of tumors per mouse. This loss of efficacy is probably due to increased resistance acquired by the more advanced neoplastic lesions as they become more compact and refractory to the immune mechanisms thus activated (43,44). The growth of these lesions is fatal, even if the expansion of smaller lesions is still controlled by the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ectopically applied collagenase, or a reduced accumulation of collagen fibrils in tissue, correlates with enhanced 'drug' delivery to tumors Brown et al, 2003;Loeffler et al, 2006;Gade et al, 2009), thus indicating that the organization and structure of perivascular collagen fibrils regulate vascular leakage. To directly assess whether inhibition of collagenolytic MMP activity impacted vascular leakage, we used the Miles assay (Miles and Miles, 1952), which is an in vivo assay of vascular leakage, to analyze the acute cutaneous vascular response to mustard oil (MO) in mice that were pretreated systemically with the broad-spectrum metalloproteinase (MP) inhibitor GM6001.…”
Section: Loss Of Mmp14 Activity Increases Steady-state Vascular Leakagementioning
confidence: 99%
“…Reduced type I collagen accumulation enhances drug penetration and drug responses Brown et al, 2003;Loeffler et al, 2006;McKee et al, 2006), as does ectopic delivery of interstitial collagenases (Gade et al, 2009). Thus, transient blockade of TGFb would be expected to not only reduce matrix synthesis, but also to reduce perivascular and stromal cell contractility, leading to reduced interstitial fluid pressure, and improved tissue perfusion and drug delivery.…”
Section: Disease Models and Mechanisms 323mentioning
confidence: 99%